SOSIALISASI DAN EDUKASI PENYAKIT ANEMIA SERTA PENGGUNAAN OBAT TABLET TAMBAH DARAH PADA SISWA-SISWI DI SMAN 8 KENDARI - Fery Indradewi Armadany; Astrid Indalifiany; Azzahra Muhareva; Hirona Roman Pabendon; Nuraini Nuraini; Suci Lestari; Yusmin Marifatul Janah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Anemia remains a major global health problem, particularly in developing countries such as Indonesia. Clinically, anemia occurs when hemoglobin levels in the blood fall below normal values, reducing the blood’s ability to transport oxygen to body tissues. Anemia is commonly found among adolescents and is often associated with a lack of knowledge regarding the importance of consuming Iron Supplement Tablets (TTD). This community service activity aimed to improve adherence to Iron Supplement Tablet consumption as an effort to prevent anemia among students of SMAN 8 Kendari. The program involved the distribution of Iron Supplement Tablets and health education using lecture methods supported by visual media, including presentation slides and leaflets. A discussion and question-and-answer session was also conducted to encourage participant engagement and understanding. The results of the activity showed that participants gained a better understanding of anemia, its prevention, and the proper use of Iron Supplement Tablets. In conclusion, the students of SMAN 8 Kendari demonstrated increased knowledge and awareness regarding anemia and the appropriate use of Iron Supplement Tablets, indicating that educational interventions can contribute to anemia prevention among adolescents.